Taxonomy and phylogeny of the genus Sensillanura Deharveng, 1981 (Collembola: Neanuridae: Neanurinae) with description of six new species from the Southern Appalachian Mountains of North America - Smolis, Adrian; Arango, Angela; Bernard, Ernest C.; Palacios-Vargas, José G. (Zootaxa, 2026)
Six new species of the genus Sensillanura Deharveng, 1981 from the Appalachian Mountains of North America are described: S. snideri sp. nov., S. marimutti sp. nov., S. sotoadamesi sp. nov., S. giribeti sp. nov., S. subiasi sp. nov. and S. boneti sp. nov. Additions to the description of Sensillanura bullsa (Wray, 1953) are also included and new records for S. santizaragozai are given. An attempt to resolve the phylogeny of the tribe is done, with a cladistic analysis based on 137 external morphological characters of 30 species. An identification key for the species on the genus and the updated generic diagnosis is provided. A discussion of the biogeographical distribution of the Sensillanurini is also included.